When to show who you are or who you could be : personnel selection and finding the right person for the job - Jacksch, Vanessa; Justus Liebig University Giessen (My University, 2018)
Overall, the following line or research aims to explore and carefully investigate not only several factors influencing candidates´ behaviours and performance during personnel selection but also to take a close look at several different selection tools or situations. The first study explores how impression management plays a role during the very first contact a candidate has with a potential new employer. Impression management (IM) is a constant concern during personnel selection. For one, during an interview or assessment exercise such IM can influence decision making (e.g., Barrick & Mount, 1996; Ellis, West, Ryan, & DeShon, 2002a). First impressions count, thus IM behaviors can influence the impression an candidate leaves even during the first contact point between candidate and employer, yet no study to date has explored whether candidates already engage in IM behaviors during the first step of their application, i.e., in their cover letters and curriculum vitaes (CV). The first study coded cover letters and CVs on IM tactics and shows that candidates indeed engage in several IM tactics, and further illustrates which IM tactics are used and when. Additionally, the study examines if some people tend to use IM throughout the selection process or whether it depends on the assessment situation, as well as which individual antecedents may influence IM behavior. The second study of this line of research focuses on another form or impression management, i.e. response distortion on personality tests. Candidates often distort their responses on personality questionnaire items. Besides the well documented score inflations on desirable items, this distortion causes a second phenomenon in the form of an additional ideal-employee factor (IEF) underlying responses of items from diverse personality dimensions. Less explored is how the IEF evolves and what pattern it has. The first part of the second study tests the emergence of the IEF among true applicants, i.e., whether applying for different jobs leads to different personality items loading onto the IEF. The second part of the second (experimental) study shows that different job profiles may predict how an applicant scores on the big five personality items and, therewith, how the IEF is formed. It further addresses and supports the relevance of the individual and situational antecedents of response distortion as proposed by McFarland and Ryan (2000). The last study of this line of research focuses less on what candidates do or do not do, but rather on what the selection tool or the presentation thereof can cause. Past research suggests that transparency during personnel selection procedures, i.e., revealing to candidates the dimensions on which their performance is being assessed, increases both fairness and candidates´ performance. Two experiments challenge this assumption and propose that this effect only holds for non-threatening performance dimensions. Yet, when the dimension revealed targets candidates with a negative stereotype, their performance may suffer. In the first part of this study, both men and women performed better when they learned that a selection simulation targeted planning skills. Yet, when women learned that the simulation targeted leadership skills, they performed worse. The second part of this study revealed a marginally significant interaction between transparency condition, gender, and stigma consciousness. In summary, transparency during personnel selection may thus benefit only some groups of candidates while hurting others.
Keywords: ddc:150